Antibactrial Activity of Asteriscus graveolens Methanolic Extract: Synergistic Effect with Fungal Mediated Nanoparticles against Some Enteric Bacterial Human Pathogens (Journal of Basic and Applied Research in Biomedicine, 2022)
Antibactrial activity of Asteriscus graveolens methanolic extract and its synergy effect with fungal mediated silver nanoparticles (AgNPs) against some enteric bacterial human pathogen was conducted. Silver nanoparticles were synthesized by the fungal strain namely Tritirachium oryzae W5H as reported early. In this study, MICs of AgNPs against E. aerogenes, Salmonella sp., E. coli and C. albicans in order were 2.13, 19.15, 0.08 and 6.38 µg/mL, respectively, while the MICs of A. graveolens ethanolic extract against the same bacteria were 4, 366,